'Phantom' atoms and thermal motion in fullerene C60 revealed by x-ray and neutron diffraction. (30th August 2021) - Nigmatullina, E K; Kibalin, I A; Sedov, V P; Borisenkova, A A; Bykov, A A; Golosovsky, I V
Abstract: The additional atomic occupancy in the octahedral and the tetrahedral voids of the face-centered cubic lattice (fcc) of fullerene C60 was detected by neutron and x-ray powder diffraction. The observed occupancy exactly tracks the rearrangement of the orientation order with temperature decreases and results from the large atomic vibrations of the carbon atoms constituting the fullerene molecules. This motion assumes a small but finite probability to find the carbon atoms in the fcc interstitial voids, which is modeled by the detected 'phantom' occupancies.